Phosphorus Mobilization in Flooded Riparian Soils From the Lake Champlain Basin, VT, USA - Young, Eric O.; Ross, Donald S. (Frontiers in Environmental Science, 2018)
Riparian zones can release bioavailable phosphorus and contribute to water quality degradation. Here, we measured phosphorus (P) release to soil porewater (PW) and overlying floodwater (FW) in 12 riparian buffer and 2 agricultural floodplain soils from northwestern Vermont, USA. The objective was to measure P desorption potential and mobilization to floodwater under moderately reducing conditions designed to mimic saturated riparian environments. Duplicate samples (field-moist) were flooded with distilled water in polyethylene beakers modified for PW sampling. Soluble reactive P (SRP) (PW and FW) and PW ferrous iron (Fe2+) were measured over a 75-day period in the laboratory. Soluble unreactive P (SUP) in PW was also measured twice. Samples from two sites were also flooded after air-drying to assess the effect of drying soil on SRP release. Results indicated PW-SRP tended to increase over time, whereas FW-SRP tended to decrease. The ratio of PW-SRP on day-75 to initial concentrations ranged from 0.21 to 8.4 (mean = 3.2 ± 2.7), while the ratio for FW-SRP was 0.19 to 1.3 (mean = 0.63 ± 0.39). Mean PW- and FW-SRP ranged from 0.03 to 2.2 mg/L and 0.01 to 0.33 mg/L, respectively. Reduction occurred in 13/14 soils as indicated by PW-Fe2+, while FW remained oxidized. Mean PW- (R2 = 0.48, P = 0.006) and FW-SRP (R2 = 0.47, P = 0.007) increased with pH, whereas PW-SUP increased at lower pH (R2 = 0.44, P = 0.01). Mean ratio of PW-SRP:FW-SRP was 3.5 ± 1.9 and increased with soil pH (R2 = 0.59, P = 0.001). Modified Morgan extractable P was a good predictor of both mean FW- (R2 = 0.75, P < 0.0001) and PW-SRP (R2 = 0.77, P < 0.0001) and release over time. Flooding air-dried soil decreased FW dissolved oxygen concentrations and increased PW-Fe2+, PW-SRP, and SRP mobilization to FW relative to a field-moist state. Results indicate that while PW-SRP release was substantial, mobilization to overlying FW was limited by resorption of released P. Our results highlight the importance of integrating labile soil P measures with hydrologic flow pathways in models to better predict P transport in riparian landscapes.